Pengaruh lama waktu perendaman terhadap arakteristik gelatin ceker ayam - Miskiyah Miskiyah; Kirana Sanggrami Sasmitaloka; Agus Budiyanto (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
Gelatine is a protein derivative that can be obtained from collagen fibres through the extraction process. The soaking duration process will affect to quality of gelatine. Research was conducted to analyzed the effect of soaking time using acid-base combination on the characteristics of chicken feet gelatine. Design used in this study was a randomized block design with six replications. Treatment used was soaking time treatment (2, 4, and 8 hours). The resulting gelatine was analyzed for physicochemical characteristics. Results showed that curing time significantly (P 0.05) on water content, ash content, fat content and pH, but not significantly (P 0.05) on yield, protein content, viscosity, gel strength, time of gel formation and melting time. Gelatine produced with 4 hour soaking time produced the best characteristic of chicken feet gelatine with a yield of 3.51 ± 0.26 %, moisture content of 7.01 ± 1.09 %, ash content of 3.09 ± 0.02 %, fat content of 2.09 ± 0.43 %, protein content 78.40 ± 0.68 %, soluble, viscosity 12.20 ± 0.70 cP, gel strength 56.94 ± 23.75 bloom, pH 6.58 ± 0.03, gelling time 326.67 ± 20.55 seconds and melting time 230.67 ± 163.7 seconds.